1997
DOI: 10.1007/s004670050308
|View full text |Cite
|
Sign up to set email alerts
|

A controlled study of deflazacort in the treatment of idiopathic nephrotic syndrome

Abstract: Forty patients with steroid-dependent idiopathic nephrotic syndrome (INS), a mean follow-up of 5.5 years, and a mean number of relapses of ten were blindly assigned to either deflazacort (DFZ) (n = 20) or prednisone (PDN) (n = 20) according to a ratio of equivalence of DFZ/ PDN = 0.8. This treatment was given for 1 year. The number of relapses was significantly lower in patients receiving DFZ. After 1 year, 12 remained in remission with DFZ compared with 2 with PDN. Growth velocity was not different in the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 12 publications
3
48
0
1
Order By: Relevance
“…Deflazacort [14,15,24] significantly reduced the number of children with steroid-dependent SSNS who relapsed during therapy (40 children; RR 0.44; 95% CI 0.25-0.78), without significant differences in side effects.…”
Section: Deflazacortmentioning
confidence: 93%
“…Deflazacort [14,15,24] significantly reduced the number of children with steroid-dependent SSNS who relapsed during therapy (40 children; RR 0.44; 95% CI 0.25-0.78), without significant differences in side effects.…”
Section: Deflazacortmentioning
confidence: 93%
“…Only three studies were analysed on an intention to treat basis 2226 28 Fewer than 10% of participants were excluded in seven studies 19-2426Only one study28 reported that outcome assessment was blinded.…”
Section: Resultsmentioning
confidence: 99%
“…26 28 Fewer than 10% of participants were excluded in seven studies 19-2426Only one study28 reported that outcome assessment was blinded. However, most studies reported the primary outcome measure using the ISKDC's definition of relapse 5…”
Section: Resultsmentioning
confidence: 99%
“…Their adverse effects on body growth, body composition, bone mineralization, and other organ functions restrict the application in grafted children and adolescents. Attempts to replace conventional glucocorticoids by deflazacort (DFZ), a methyloxazoline derivative of prednisone [1], have suggested that this agent exerts a similar anti-inflammatory and immunosuppressive action in various clinical conditions, associated with fewer side effects on bone mineralization, growth, blood pressure (BP), and metabolism [2,3,4,5,6,7]. There are only a few studies of the application of DFZ for immunosuppression after TX in adults [8,9,10] and children [11,12], and most are restricted to short observation periods.…”
Section: Introductionmentioning
confidence: 99%